El rondo training methode on passing accuary in football - Ramadhan, Racha; Afrinaldi, Rolly; Nasution, Nana Suryana (Universitas Suryakancana, 2023)
This study examines the effect of the el rondo training method on passing accuracy in SMPN 2 Rengasdengklok extracurricular. This study uses a quantitative approach. The primary data collection was gained through the pre-test and post-test results on extracurricular students at SMPN 2 Rengasdengklok. The results of this study indicate that: 1). The normality test has a pre-test value with a significance of 0.091 > 0.05 and a post-test with a significance of 0.134 > 0.05, indicating the normally distributed data. 2). The pre-test and post-test homogeneity tests have a value of 0.939 > 0.05, meaning that the data is homogeneous. 3). Hypothesis testing was carried out with a t-count value of 27.358 and t-table 2.06360 with a significance (2-tailed) of 0.000 <0.05. It means that the el rondo training method has a significant effect on the accuracy of passing in extracurricular football at SMP 2 Rengasdengklok. 4). Having carried out the post-test, there was an increase in the ability of 51%. This study concludes that the el rondo training method has a significant effect on the accuracy of passing in soccer extracurricular at SMP 2 Rengasdengklok.Key words: El Rondo Training Method, Accuracy Passing, extracurricular